Cover Feature: Analysis of 2D DNA Origami with Nanopipettes (ChemElectroChem 20/2018). Issue 20 (12th September 2018) - Raveendran, Mukhil; Lee, Andrew J.; Wälti, Christoph; Actis, Paolo
Abstract : The Cover Feature illustrates a nanopipette as a barcode reader that can distinguish different DNA origami structures of similar size with single‐entity resolution. More information can be found in the Article by M. Raveendran et al. onpage 3014 in Issue 20, 2018 (DOI:10.1002/celc.201800732 ).